2007
DOI: 10.1016/j.nuclphysa.2006.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Hadron Correlations and Parton Recombination

Abstract: Parton recombination has been found to be an extremely useful model to understand hadron production at the Relativistic Heavy Ion Collider. It is particularly important to explore its connections with hard processes. This article reviews some of the aspects of the quark recombination model and places particular emphasis on hadron correlations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
(29 reference statements)
0
4
0
Order By: Relevance
“…The related low-p T issues of QCM such as entropy conservation and pion production have been properly addressed [12,20,[25][26][27][28][29]. There are also many successful applications of QCM on correlation studies, e.g., multi-hadron yield correlations [15][16][17]30], baryon-meson correlated emission [31,32] as well as the charge balance function [33,34]. …”
Section: Yields Of Strange Hadrons At Lhcmentioning
confidence: 99%
“…The related low-p T issues of QCM such as entropy conservation and pion production have been properly addressed [12,20,[25][26][27][28][29]. There are also many successful applications of QCM on correlation studies, e.g., multi-hadron yield correlations [15][16][17]30], baryon-meson correlated emission [31,32] as well as the charge balance function [33,34]. …”
Section: Yields Of Strange Hadrons At Lhcmentioning
confidence: 99%
“…A predicted higher energy loss for in-medium gluons should then result in even larger jet-like yields for non-pion triggers [41]. On the other hand, particle production from recombination should produce smaller yields than particle production from hard processes (fragmentation) [30], thus diluting (reducing) per-trigger associated yields. This dilution effect would be stronger for baryons, as more intermediate-p T baryons than mesons are expected to be formed through such a mechanism.…”
mentioning
confidence: 97%
“…This kinematic range focuses on a particularly interesting region where trigger particle production is thought to be dominated by fragmentation, at least in pp and d+Au collisions. For the same range in Au+Au events, the baryon-to-meson enhancement is large, suggesting significant recombination contributions [30]. Since the medium induced jet quenching affects the correlations in essentially an opposite way from thermal parton recombination contributions, comparing the correlations for proton and pion triggers provides an additional handle for separating these effects.…”
mentioning
confidence: 99%
“…Recombination models incorporating coalescence of two or three thermal quarks to form a meson or a baryon are able to reproduce the observed enhancement [4,5]. In di-hadron analyses, recombination of thermal quarks into a hadron in the trigger p T range would lead to a 'trigger dilution' effect: more intermediate p T baryons than mesons without correlated jet-like yield would lead to a lower associated per-trigger yield at small relative angles for a correlation measurement using baryons as leading particles compared to mesons [6,7]. This expectation has not been conclusively confirmed by previous correlation studies with identified triggers [8,9].…”
mentioning
confidence: 97%